EXPERIMENTAL STUDY OF THE DRYING PROCESS OF MEDICINAL PLANTS - Sultanova, A.; Safarov, J. E. (International Journal of Psychosocial Rehabilitation, 2020)
On a solar-water convective drying oven, experimental studies were performed and curves of the duration and temperature of the drying process of medicinal plants were obtained. Based on the results of experimental studies of the dehydration process at the installation, an engineering methodology has been developed for calculating the design and technological parameters of an industrial solar-water convective installation.